GAMBARAN HIPOGLIKEMIA PADA BAYI BARU LAHIR - Dewi Adinda Paramita; Purwanti, Indri Astuti; Nuke Devi Indrawati; Siti Nurjanah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2023)
Hypoglycemia actually is a natural process in newborn adaptation but can cause damage and delays in the baby's brain development. The incidence of hypoglycemia at Harapan Anda Islamic General Hospital (RSU) in the January-September 2022 period is about 153 newborns. Risk factors that can cause hypoglycemia are gestational age and birth weight. This study aims to describe the incidence of hypoglycemia in Harapan Anda Islamic General Hospital and the characteristic of bitrh weigh and gestational age. This study uses a descriptive method with a cross sectional approach. The population of this study is 153 newborn from Januari-September 2022 period. Technical Sampling was using randomized sampling and calcutated using Slovin Formula and has obtained 60 samples. All samples has met the inclusion and exclusion criteria This type of data was using secondary data where the data is obtained from the patient's medical record. The result of this stuy shows that, there were 40 cases (66.67%) of gestational age classified as premature, 42 cases (70%) of low birth weight, and 42 cases of hypoglycemia (70%). Hypoglycemia and Low Birth Weight are the most common problems in newborns at RSU Islam Harapan Anda, followed by premature births.